2021
DOI: 10.3390/en14092512
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Selected Wells Operational Power with Borehole Heat Exchangers Operating in Real Conditions, Based on Experimental Tests

Abstract: On the basis of experimental studies, the operational power of four borehole heat exchangers (BHE) under real conditions was determined. The research was carried out in 2018–2019. The theoretical power of the BHE was verified with its operating power. The amount of thermal energy absorbed from the ground by individual BHEs, the operating temperatures obtained at the inlet and outlet of the exchanger, the annual brine flow rate, and the average operating power of the tested wells in two heating seasons were com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 67 publications
0
14
0
Order By: Relevance
“…[79]. The annual insolation was 1961.9 kWh/m 2 •year [80] and was higher than the insolation from the standard period 1991-2020, which is 1755.3 kWh/m 2 •year (Table 2). In the second zone, at a depth of 5 m to 12 m, ground temperature changes in individual months of the year are less intense than in the first layer.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…[79]. The annual insolation was 1961.9 kWh/m 2 •year [80] and was higher than the insolation from the standard period 1991-2020, which is 1755.3 kWh/m 2 •year (Table 2). In the second zone, at a depth of 5 m to 12 m, ground temperature changes in individual months of the year are less intense than in the first layer.…”
Section: Resultsmentioning
confidence: 99%
“…The maximum well power determined during the tests using the TRT test was 3.54 kW, with the operating time of the compressors up to 2000 h/year. Experimental measurements in 2018 and 2019 showed that the tested BHE wells during their operation did not reach their maximum power of 3.54 kW, determined by the TRT test, and the operating time of heat pump compressors exceeded 2000 h/year [80].…”
Section: Experimental and Measuring Sitementioning
confidence: 99%
See 3 more Smart Citations